The Cambridge companion to Greek and Roman theatre - McDonald, Marianne; Walton, John Michael (The Cambridge companions to literature and classics, 2007)
This series of essays by prominent academics and practitioners investigates in detail the history of performance in the classical Greek and Roman world. Beginning with the earliest examples of 'dramatic' presentation in the epic cycles and reaching through to the latter days of the Roman Empire and beyond, this 2007 Companion covers many aspects of these broad presentational societies. Dramatic performances that are text-based form only one part of cultures where presentation is a major element of all social and political life. Individual chapters range across a two thousand year timescale, and include specific chapters on acting traditions, masks, properties, playing places, festivals, religion and drama, comedy and society, and commodity, concluding with the dramatic legacy of myth and the modern media. The book addresses the needs of students of drama and classics, as well as anyone with an interest in the theatre's history and practice.